Effect of COVID 19 on Mental Health Status of Health Care Providers Working in a District Medical College Hospital of West Bengal - A Questionnaire-Based Study - Biswas , S; Das , A (Journal of Indian Academy of Forensic Medicine, 2023)
COVID-19 has become a threat to human civilization since its outbreak. Doctors, nurses, and other health care workers (HCWs) have been detected COVID-19 positive across the country and many of them have lost their lives too. Not only them but also their family members and close ones are susceptible to the infection. Fear of getting infected, losing near and dear ones, and social ostracization have led to unprecedented psychological stress among health care workers. The objective of this study is to know about the prevalence of depression, anxiety, and stress among the said population and their attitude and knowledge about COVID-19 and to establish any correlation between these parameters. It was a cross-sectional study done at Rampurhat Govt. Medical College, West Bengal, India over a period of 2 months on 150 subjects. DASS 21 scale was used for scoring depression, anxiety, and stress level. Prevalence of depression, anxiety, and stress was studied and their correlation with knowledge, attitude, and demographic factors were studied. The prevalence of depression, anxiety, and stress noted in this study is 34.7%, 50.7% and 34.7% respectively. Statistically significant correlations between depression and age, anxiety and occupation-gender, stress, and COVID positive family history were established. COVID-19 is an important factor for mental health among the health care providers which in turn is affected by other demographic factors. This must be dealt accordingly to ensure maximum service from the health care workers for the society.